Assessment of fluoride intake from groundwater and intake reduction from delivering bottled water in Chiang Mai Province, Thailand - Benyapa Sawangjang (2019)
© 2019 Fluoride intake from tap water supplied by fluoride-containing groundwater has been the primary cause of fluorosis among the residents of Buak Khang Subdistrict, Chiang Mai Province, Thailand. To reduce fluoride intake, bottled water treated using reverse-osmosis membranes has been made available by community-owned water treatment plants. This study aimed to assess the resultant reduction in fluoride intake from using bottled water for drinking and cooking. Water consumption surveys were conducted by providing bottled water to 183 individuals from 35 randomly selected households and recording the amount of water consumed for drinking and cooking. The mean drinking water consumption was 1.62–1.88 L/capita/day and the cooking water consumption on weekends (5.06 ± 3.04 L/household/day) was higher than that on weekdays (3.80 ± 1.90 L/household/day). The per capita drinking water consumption exhibited a positive correlation with body weight; however, the low-weight subjects consumed more drinking water per kilogram of body weight than the heavy subjects. Although sex and day of the week did not significantly affect drinking water consumption per capita, girls consumed less water in school possibly due to their group mentality. Drinking water consumption per kilogram of body weight was significantly higher among women, children, and the elderly because these groups generally have low body weights. The fluoride intake from using tap water for drinking and cooking was estimated to be 0.18 ± 0.10 mg/kg-body weight/day and 5.55 ± 3.52 mg/capita/day, respectively, whereas using bottled water for drinking and cooking reduced the fluoride intake to 0.002 ± 0.002 mg/kg-body weight/day and 0.07 ± 0.05 mg/capita/day, respectively. Despite the increased cost, 98% and 90% of the subjects selected bottled water over tap water for drinking and cooking, respectively; thus, bottled water delivery services could be used to mitigate fluoride intake in developing countries.